3D-Printed Electromagnetic Band-Gap Band-Pass Filter Based on Empty Single-Ridge Waveguide - Hector Garcia-Martinez; German Torregrosa-Penalva; Ernesto Avila-Navarro; Nicolo Delmonte; Lorenzo Silvestri; Maurizio Bozzi (IEEE Access, 2022)
In this work, a new method for the design of band-pass filters in an empty waveguide by using periodic structures is presented in a theoretical and experimental way. The proposed filter topology uses a periodic profile of two heights in the central part of an Empty Single-Ridge Waveguide (ESRW) for the generation of an Electromagnetic Band-Gap (EBG), and it provides simple unit cell design parameters to produce specific dispersion characteristics. The implementation of two band-pass filters with different fractional bandwidths (36% and 55%) and different characteristics in the rejection band is proposed, where to minimize the mismatch in the ESRW filter’s passband, a tapering technique is used that follows a Kaiser distribution for the EBG. To experimentally validate the design concept, a band-pass filter with a fractional bandwidth of 55% centered on 5.45 GHz is manufactured, using a low-cost 3D printer, which allows the rapid manufacture of complex geometries at a very reduced price. The experimental results validate the simulated response of the implemented ESRW band-pass filter.